The Use of Livemocha: A Platform for Independent Language Learning - Wahyu Indah Mala Rohmana (Abjadia, 2022)
The Covid -19 pandemic has affected all aspect of human’s life including the educational institution. All the activities are then held mostly online. Many online platform are used as a tool to interact between teacher and students.  Despite their massive growth in online teaching, little research has been conducted about the use of online language learning community in learning foreign language. The aim of this study  is to examine the use of Livemocha to learn foreign language independently. This study uses autoethnography method which uses the researcher personal experience to describe and analyze the data. Result of this study shows that the site is useful for learning English independently. This study concludes with suggestions for English Learning through social networking site.